The influence of parachute-resisted sprinting on running mechanics in collegiate track athletes - Paulson, S.; Braun, W. A. (The Journal of Strength and Conditioning Research, 2011)
The influence of parachute-resisted sprinting on running mechanics in collegiate track athletes. The aim of this investigation was to compare the acute effects of parachute-resisted (PR) sprinting on selected kinematic variables. Twelve collegiate sprinters (mean age 19.58 ± 1.44 years, mass 69.32 ± 14.38 kg, height 1.71 ± 9.86 m) ran a 40-yd dash under 2 conditions: PR sprint and sprint without a parachute (NC) that were recorded on a video computer system (60 Hz). Sagittal plane kinematics of the right side of the body was digitized to calculate joint angles at initial ground contact (IGC) and end ground contact (EGC), ground contact (GC) time, stride rate (SR), stride length (SL), and the times of the 40-yd dashes. The NC 40-yd dash time was significantly faster than the PR trial (p < 0.05). The shoulder angle at EGC significantly increased from 34.10 to 42.10° during the PR trial (p < 0.05). There were no significant differences in GC time, SR, SL, or the other joint angles between the 2 trials (p > 0.05). This study suggests that PR sprinting does not acutely affect GC time, SR, SL and upper extremity or lower extremity joint angles during weight acceptance (IGC) in collegiate sprinters. However, PR sprinting increased shoulder flexion by 23.5% at push-off and decreased speed by 4.4%. While sprinting with the parachute, the athlete's movement patterns resembled their mechanics during the unloaded condition. This indicates the external load caused by PR did not substantially overload the runner, and only caused a minor change in the shoulder during push-off. This sports-specific training apparatus may provide coaches with another method for training athletes in a sports-specific manner without causing acute changes to running mechanics.